The race to disasters - is the international relief community ready for future disasters? - Kobi Peleg; Moran Bodas (Israel Journal of Health Policy Research)
Abstract Background Climate-related disasters have tripled in the past 30 years. Between 2006 and 2016, the global sea levels rose 2.5 times faster than the entire 20th century. More than 20 million people a year are forced out of their homes because of climate change impacts. Rapid urbanization and increasing population density in coastal mega-metropolitan areas will inevitably lead to more large-scale disasters due to extreme weather events, i.e., stronger storms and massive flooding. Despite the inevitability of these events, disaster risk reduction is still locally based in each country, many of which have scarce resources to devote to the activity. It is widely assumed that the global community will respond when a calamity occurs. This perspective article explores the appropriateness of the current international relief and aid paradigm in light of near and middle-term trends in global disasters. Main body After briefly summarizing the anticipated effects of global climate change, population growth, and progressive urbanization in low-lying coastal and riverine environments on the frequency and scale of future disasters, this paper examines how existing concepts of international relief following disasters are insufficient to address the challenges to come. Current paradigms are tested against selected case studies demonstrating the growing frequency of mega-disasters. For example, in 2010, the world saw a catastrophic earthquake in Haiti, very large-scale floods in Pakistan, a major earthquake in Chile, and heat waves that resulted in the death of tens of thousands of people in Russia and many more in other countries. However, the world exhausted most of its humanitarian aid, responding to Haiti in January of that year. The review closes with a proposition for a new paradigm to re-organize international relief to meet the challenge posed by our rapidly changing world – one that is more adaptable to the current challenges of climate change and other trends that will almost certainly increase the frequency and intensity of disasters. Conclusion The future of international disaster aid depends on our ability to foster greater cooperation between the various organizations and donor countries and more seamless cooperation between both groups and the affected countries or regions. Planning and relief operations should utilize new technologies and innovative financing where feasible. A holistic approach that focuses on building large-scale agreements and coordination mechanisms, teaching citizens how to help each other until aid arrives, and strengthening resilience at the local level will equip communities for adaptive action during a disaster, improve coping and long-term rehabilitation, will lead to a more efficient, fairer and more durable global aid system.